2011
DOI: 10.1080/07391102.2011.10507392
|View full text |Cite
|
Sign up to set email alerts
|

Prevalent Mutations of Human Prion Protein: A Molecular Modeling and Molecular Dynamics Study

Abstract: Point mutations in the human prion protein gene, leading to amino acid substitutions in the human prion protein contribute to conversion of PrPC to PrPSc and amyloid formation, resulting in prion diseases such as familial Creutzfeldt-Jakob disease (CJD), Gerstmann-Straussler-Scheinker disease (GSS), and fatal familial insomnia. We have investigated impressions of prevalent mutations including Q217R, D202N, F198S, on the human prion protein and compared the mutant models with wild types. Structural analyses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…[34] Some computational studies carried out on either wt PrP or pathogenic mutant variants revealed increased structural dynamics in a1 because of the movement of a1a way from a2-a3. [35,36] The antibody ICSM 18, which is known to bind to both a1a nd parts of a3, [37] has one of the highest therapeutic potencies for PrP,p resumably because it locks PrP and prevents its subdomain separation. Molecules that stabilize the Cterminus of a2h ave also proved to be effective antiprion drugs, both ex vivo and in vivo, [38] and most likely act by inhibiting step 2o fP rP misfolding.H ence,t he current study indicates that the inhibition of either step 1orstep 2ofPrP misfolding by the use of chemical chaperones or drugs would have therapeutic value.…”
Section: Methodsmentioning
confidence: 99%
“…[34] Some computational studies carried out on either wt PrP or pathogenic mutant variants revealed increased structural dynamics in a1 because of the movement of a1a way from a2-a3. [35,36] The antibody ICSM 18, which is known to bind to both a1a nd parts of a3, [37] has one of the highest therapeutic potencies for PrP,p resumably because it locks PrP and prevents its subdomain separation. Molecules that stabilize the Cterminus of a2h ave also proved to be effective antiprion drugs, both ex vivo and in vivo, [38] and most likely act by inhibiting step 2o fP rP misfolding.H ence,t he current study indicates that the inhibition of either step 1orstep 2ofPrP misfolding by the use of chemical chaperones or drugs would have therapeutic value.…”
Section: Methodsmentioning
confidence: 99%
“…114 Several computational studies have showed increased structural dynamics in the α1 region during the early stages of PrP misfolding. 115,116 Page 10 of 44 Biochemistry 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 11 The loop between β2 and α2 is another region that has been suggested to be critical for the misfolding of PrP. 117 The conformation and rigidity of this loop appears to determine prion disease transmission and susceptibility of a species.…”
Section: Structural Similarity Between Amyloid Fibrils and Soluble Olmentioning
confidence: 98%
“…In human Creutzfeldt-Jakob disease, the substrate protein bears a profibrillogenic mutation. 99 It has been argued that additional molecules may be involved; however, to date, none has been definitively identified. Amyloidogenic mutations in lysozyme also create a fibrillogenic precursor molecule that does not require proteolytic cleavage to initiate fibril formation in vivo.…”
Section: Heterogeneity In Disease-associated Amyloidogenesismentioning
confidence: 99%